Productivity and nutrient uptake of pigeonpea (Cajanus cajan) in pigeonpea based intercropping systems as influenced by planting pattern and nutrients levels applied to intercrops - SEKHON, FATEHJEET SINGH; SINGH, THAKAR; SAINI, K S (The Indian Journal of Agricultural Sciences, 2018)
The experiment was conducted at students’ research farm, Punjab Agricultural University, Ludhiana during 2015 and 2016 to study the effect of planting pattern and levels of nutrient applied to intercrops on growth, yield and nutrient uptake in pigeonpea [Cajanus cajan (L.) Millsp.] based intercropping systems. Pigeonpea seed yield and biological yield were not significantly influenced by different planting pattern and nutrient level applied to intercrops under different intercropping systems during both the years. Pigeonpea equivalent yield was significantly affected by planting pattern and nutrient levels. Highest pigeonpea equivalent yield (1.84 and 1.90 tonnes/ha) was observed under planting pattern of pigeonpea (50 cm × 25 cm) + maize fodder during during both the years. Pigeonpea equivalent yield increased with increase in levels of nutrient to intercrops and maximum pigeonpea equivalent yield of 1.63 and 1.73 tonnes/ha was obtained with 100% of recommended dose of nutrients applied to intercrop. N, P and K uptake by pigeonpea was not affected by different planting pattern but N (75.3 and 80.8 kg/ha), P (16.0 and 17.2 kg/ha) and K (70.0 and 78.4 kg/ha) uptake was maximum with 100% nutrients applied to intercrops during both the years, respectively. Similar trend was observed with available N, P and K in soil at harvest.